Penerapan Spare Parts Inventory Management System berdasarkan Klasifikasi VESO dan RECOM untuk mengurangi searching time pada perusahaan manufaktur komponen otomotif - Widya, Adi Rusdi; Rahardjo, Sugeng Budi (DPPM UNIVERSITAS PELITA BANGSA, 2022)
Spare parts components are important to be managed properly, if the availability of spare parts is not considered it can cause production machines to stop operating. This is a consideration by the company to manage spare parts that can be controlled properly. The large number of machine components that vary with different types and types of machines causes the spare part controller to be able to arrange, give names, signs and labels, and store them to make it easier to search for these parts when needed for the process of replacing damaged parts. The parts availability management system requires data needs based on the type & type of machine, uniformity in mentioning the names of parts, functions and forms. Before the implementation of the parts keeper management system, it takes 35 minutes to find and get the parts needed. By applying the VESO and ROCEM classification methods, it can help in grouping, storing, and assisting in making component naming standards and determining how many parts are needed on an ROP basis. This system can help the search time for machining parts to be 16 minutes so that there is a reduction in service time in the need for these parts by 54% faster than the system before spare part management was carried out.